Comparison of the effect of ginger and zinc sulfate on primary dysmenorrhea: A placebo-controlled randomized trial - Kashefi, F.; Khajehei, Marjan; Tabatabaeichehr, M.; Alavinia, M.; Asili, J. (W.B. Saunders Co., 2014)
Primary dysmenorrhea is common among young women and results in their incapacitation; it can be accompanied by various symptoms that can disrupt their lives. The aim of this randomized trial was to compare the effect of ginger, zinc sulfate, and placebo on the severity of primary dysmenorrhea in young women. One hundred and fifty high school students were recruited. The participants were divided into three groups. The first group received ginger capsules, the second group received zinc sulfate capsules, and the third group received placebo capsules. All participants took the medications for four days, from the day before the commencement of menstruation to the third day of their menstrual bleeding. The severity of dysmenorrhea was assessed every 24 hours by the pain visual analog scale. The severity of pain was significantly different between, before, and after the intervention in both the ginger and the zinc sulfate groups (p < .001). Compared with the placebo receiving group, participants receiving ginger and zinc sulfate reported more alleviation of pain during the intervention (p < .05). Ginger and zinc sulfate had similar positive effects on the improvement of primary dysmenorrheal pain in young women.